Transformational Leadership on Women's Leadership in Islam - Kana Safrina Rouzi; Halim Purnomo; Muh. Mustakim; Faisal Bin Husen Ismail (Journal of Feminism and Gender Studies, 2022)
This paper describes a transformational leadership review of women's leadership in Islam. This study aims to explain leadership concepts that combine women's leadership qualities (gentleness, balance, courage, feelings of compassion, wisdom and integrity) with several characteristics in transformational leadership theory which include moral, self-confidence, vision, environmental orientation, inspiring and charismatic and then integrate with the Qur'anic text on leadership in Islam. This review results that women adopt a participatory and democratic leadership style which is the character of transformational and Islamic leadership.